2008
DOI: 10.1590/s0004-27302008000400015
|View full text |Cite
|
Sign up to set email alerts
|

Níveis baixos de 25-hidroxivitamina D (25OHD) em pacientes com doença inflamatória intestinal e sua correlação com a densidade mineral óssea

Abstract: RESUMOIntrodução: Pacientes com doenças inflamatórias intestinais (DII) estão propensos a apresentar níveis baixos de vitamina D (25OHD) e densidade mineral óssea (DMO) diminuída. Objetivo: Verificar o nível de 25OHD em jovens com DII submetidos à avaliação clínica, dosagens bioquímicas rotineiras e medida da DMO de coluna lombar e fêmur, comparando-os com controles saudáveis. Resultados: 39 pacientes com doença de Crohn (DC) (p = 0, 003) e 37 com retocolite ulcerativa inespecífica (RCUI) (p < 0,001) apresenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
0
14
1
3
Order By: Relevance
“…Souza et al described that the number of patients with low BMD between the two groups of IBD is equivalent. 3 In our study, however, we observed that CD patients had a higher prevalence of bone alterations (52.6% CD and 29.6% UC, p=0.07). This difference may be related to the fact that in CD a greater area of the digestive tract implied in the absorption of nutrients is affected, or even because these patients use corticosteroids more frequently compared with patients with UC.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Souza et al described that the number of patients with low BMD between the two groups of IBD is equivalent. 3 In our study, however, we observed that CD patients had a higher prevalence of bone alterations (52.6% CD and 29.6% UC, p=0.07). This difference may be related to the fact that in CD a greater area of the digestive tract implied in the absorption of nutrients is affected, or even because these patients use corticosteroids more frequently compared with patients with UC.…”
Section: Discussioncontrasting
confidence: 69%
“…In the Curitiba area, due to its climatic characteristic of low annual insolation, there is a greater possibility of vitamin D deficiency, as already evaluated by other authors. 3,16 Regarding serum vitamin D levels, the importance of its replacement in patients with IBD has already been suggested, 17 since it has a relevant role in the health of this group of patients. In addition to the benefit in bone integrity, an improvement in the immune response is expected and, although not yet fully proven, aid in the prevention of colorectal cancer, a complication that can occur in patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of epidemiological data has documented an association between vitamin D-deficiency and increased risk of IBD [14; 15; 16], including both CD and UC [17; 18; 19; 20; 21; 22; 23; 24]. A high prevalence of vitamin D deficiency was reported in patients with established as well as newly diagnosed IBD [25; 26; 27].…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal epithelial cells (IECs) are key components of the barrier that express a high level of vitamin D receptor, a nuclear hormone receptor that mediates the biological activity of the vitamin D hormone, 1,25-dihydroxyvitamin D [4]. Epidemiological studies have established that vitamin D-deficiency is common in patients with IBD that is associated with increased risk of IBD [5,6,7,8,9,10,11,12,13,14], whereas high vitamin D intake lowers the risk of IBD [15]. …”
Section: Introductionmentioning
confidence: 99%